Optimizing Learning Management Systems for Elderly Teachers in Indonesia Using a User Experience-Based Design Thinking Approach: A Case Study at SMAN 77 Jakarta - Muhamad Nursalman; Rosa Ariani Sukamto; Ahmad Fathi Ibrahimov; Amelia Zalfa; Salma Ghaida; Natasha Adinda Cantika; Muhammad Ruby PS (Khazanah Informatika : Jurnal Ilmu Komputer dan Informatika, 2025)
Learning Management Systems (LMS) have become essential tools in educational institutions for delivering online learning experiences. Despite their widespread adoption, many elderly teachers face considerable challenges in navigating and operating these platforms, which can hinder the effectiveness of the teaching and learning process. Recognizing this issue, the present study focused on developing a more user-friendly LMS tailored specifically for elderly teachers by employing a design thinking approach. This approach, known for its human-centered and iterative nature, involves five key stages: empathy, problem definition, ideation, prototyping, and testing. The study involved 30 participants, including senior teachers, younger teachers, and LMS administrators, to ensure a comprehensive understanding of user needs and to foster collaborative development. During the empathy stage, the specific difficulties faced by elderly teachers were identified, and these insights guided the formulation of the core problems. Ideas for improving the LMS interface and functionality were generated and transformed into prototypes, which were subsequently tested and refined based on user feedback. Evaluation of the final LMS design involved expert validation in UI/UX, as well as the use of two established usability instruments: the User Experience Questionnaire (UEQ) and the System Usability Scale (SUS). Results showed significant improvements in user satisfaction and usability. The UEQ scores reached the “excellent” category, with the lowest score being 1.815, indicating high user experience across various dimensions. Additionally, the SUS score improved markedly from 50 to 76, highlighting a substantial increase in perceived usability. These findings suggest that the design thinking approach is highly effective in addressing usability issues and can lead to the development of more accessible and comfortable LMS platforms for elderly educators.